Perceived Needs, Accessibility and Utilization of Information on Scientific Goat Husbandry - Sinha, Sushil Kumar; Chander, Mahesh; Mohan, Braj; Singh, Deepa; Jena, Anupama (Indian Journal of Extension Education, 2017)
An ex-post-facto study was conducted to review the needs, accessibility and utilization of information on scientific goat  rearing, with a sample of 160 respondents in Mathura district of Uttar Pradesh. Information needs were assessed on three  point continuum i.e. most needed, needed and least needed for 34 aspects of goat husbandry. Accessibility of information  was assessed in terms of frequency of (yes/no) responses, while, information utilization was measured on three point  continuum viz frequently, sometimes and never. The investigation revealed that information regarding 'common goat  diseases with their preventive measures', 'vaccination', 'local market', 'banking-finance for goat farms', and 'preparation of  economic balanced ration' were perceived extremely needed. About 85 per cent of respondents reported they had no  accessibility of relevant information in all the selected sub-areas of goat farming. Not more than 20 per cent respondents  were utilizing the accessed information frequently while more than 30 per cent of them had never used the information.
Keywords: Information; needs; goat husbandry; Uttar Pradesh